O Problema do Reconhecimento de Voz Offline em Dispositivos Móveis: em Busca de uma Abordagem Racional - Debatin , Lucas; Haendchen Filho , Aluizio; Dazzi, Rudimar L. S. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2017: Anais Estendidos do XXIII Simpósio Brasileiro de Sistemas Multimídia e Web, 2017)
This paper presents a systematic review of the literature on the subject of continuous offline voice recognition for Android mobile devices. We examined 222 articles from four digital repositories, which followed a methodology containing search questions, search expression, and inclusion and exclusion criteria. After reading the abstract, introduction and conclusion, 12 articles were selected and synthesized through answers to the research questions. Based on the synthesis, we provide information on how to select the best practices for neural networks utilization, and also suggest techniques for reducing error rate.1